Botanical Latin : history, grammar, syntax, terminology, and vocabulary - Stearn, William T. (David & Charles, 1992)
"First published in 1966, Botanical Latin has become accepted worldwide as the standard work of reference on this important subject. A comprehensive guide to every aspect of Latin usage in this field, it is an invaluable source of accurate information for gardeners, botanists, scientific historians, systematic etymologists and classical scholars alike.".